Kekerasan yang dilakukan oleh Tokoh Utama dalam Novel Invisible Man Karya H.G. Wells - Suci Dian Lestari (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2023)
The violence that arises when an ambition to control makes the character of Griffin uncontrollable. Griffin is an intelligent scientist, he is very ambitious for his discovery that is to be invisible. This makes him so obsessed that he does everything for his own benefit. Day after day terrors coming up in several areas, marked by murders, robberies to some people in several areas. Griffin does all that by threatening people to help him, but in the end he ends up tragically. This study discusses about forms of violence that physical and psychological violence, and the impact of the violence on the main character Griffin in H.G Wells' novel The Invisible Man. Methods in collecting data using the read and note method. The theory used in this research is descriptive qualitative method and literary psychology. From the results of the analysis, it is concluded that the forms of violence that Griffin commits in the novel are examined into two forms of violence, the first is psychological violence and physical violence. Therefore, this study analyzes based on the characteristics of the characters.